Multi-locus sequence typing analysis of giardia duodenalis isolates among children in rural communities in Southern Palawa, Philippines - Briones, Jeanne G. (College of Public Health,University of the Philippines Manila, 2019)
Giardia duodenalis is a flagellated protist known to cause gastrointestinal disease called giardiasis. It is globally distributed and considered as the most common cause of water-borne diarrhea (WHO, 2007). It is a species complex having eight morphologically similar but genetically distinct genotypes (assemblage A-H) with inter and intra-assemblage variation (sub-assemblages and subtypes). The detection of genetic variation and heterogeneous nucleotides when isolates were analyzed using multi-locus sequence typing (MLST) has been reported in various studies. This shows that genotyping using single locus only, may conceal the true picture of G. duodenalis genetic diversity. In the Philippines, there is limited information on the genetic distribution and diversity of G. duodenalis. The aim of the study was to identify the prevalence of G. duodenalis, its assemblages, sub-assemblages, and subtypes, including its genetic variation among the children in rural communities in Southern Palawan, Philippines using multi-locus sequence analysis of the glutamate dehydrogenase (gdh) beta-giardin (bg), and triose phosphate isomerase (tpi). G. duodenalis was detected in 18.7% (n=107) of stool samples using formalin ether concentration technique (FECT) and ssu-rRNA amplification. All of the positive samples were successfully sequenced, and 95% were typed as assemblage B. The remaining 5% were typed as assemblage A. ?Assemblage swapping? was observed in one isolate (Ph13), typed as assemblage B at the gdh and bg loci and typed as assemblage A at the tpi specific locus. Moreover, 60% of the samples were amplified at the gdh locus, 55% at the tpi locus, and 45% at the bg locus. In addition, single nucleotide polymorphisms (SNPs) that may indicate genetic variation and heterogeneous nucleotides were observed within assemblage B. The presence of heterogeneous nucleotide as observed in their chromatogram and phylogenetic tree indicates mixed infection at the sub-assemblage and subtype level. Some of the reference sequences used in the current study were isolated from animal origin based on their GenBank profiles, and may considered as zoonotic geneotypes, and thus of public health importance. Since g. duodenalis is a pathogen transmitted by cyst-contaminated water, the presence of either zoonotic or anthroponotic assemblages, sub-assemblages, and subtypes of G. duodenalis may indicate that human and animal hosts were the possible source of cyst contamination in the water. The detection of two novel multi-locus genotypes (MLGs) despite the small sample size of the study may indicate that the MLGs existing in the country may be different from the previously described and identified MLGs in other countries. Also, there is a possibility that genetic diversity of G. duodenalis in the country may be underestimated. Future studies may analyze the association of G. duodenalis assemblages, sub-assemblages, subtypes, and MLGs with virulence, symptoms, and transmission patterns that can serve as a basis for more comprehensive and effective control of giardasis.